Antitussive activity of iodo-resiniferatoxin in guinea pigs. Issue 9 (27th August 2004) - Trevisani, M; Milan, A; Gatti, R; Zanasi, A; Harrison, S; Fontana, G; Morice, A H; Geppetti, P
Abstract : Background: Iodo-resiniferatoxin (I-RTX) has recently been described as an ultra potent antagonist of the transient receptor potential vanilloid-1 (TRPV1). Methods: The ability of I-RTX to inhibit cough induced by inhalation of two putative TRPV1 stimulants (capsaicin and citric acid) was tested in non-anaesthetised guinea pigs. Results: Pretreatment with I-RTX either intraperitoneally (0.03–0.3 µmol/kg) or by aerosol (0.1–3 µM) reduced the number of coughs produced by inhalation of citric acid (0.25 M) and capsaicin (30 µM) in a dose dependent manner. Capsazepine (CPZ) also reduced citric acid and capsaicin induced cough, but the activity of I-RTX was 10–100 times more potent than CPZ in all the experimental conditions tested. Conclusions: I-RTX is a novel and potent antitussive drug which inhibits cough mediated by agents possibly acting via TRPV1 activation.